2017
DOI: 10.7554/elife.28862
|View full text |Cite
|
Sign up to set email alerts
|

High lumenal chloride in the lysosome is critical for lysosome function

Abstract: Lysosomes are organelles responsible for the breakdown and recycling of cellular machinery. Dysfunctional lysosomes give rise to lysosomal storage disorders as well as common neurodegenerative diseases. Here, we use a DNA-based, fluorescent chloride reporter to measure lysosomal chloride in Caenorhabditis elegans as well as murine and human cell culture models of lysosomal diseases. We find that the lysosome is highly enriched in chloride, and that chloride reduction correlates directly with a loss in the degr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 82 publications
(120 reference statements)
8
81
3
1
Order By: Relevance
“…However, to obtain quantitative information, ratiometric reporters that are insensitive to pH are needed. For example, Clensor and MEQ-TMR-dextran have been used to show that high lumenal Cl − , caused by the activity of ClC-7, is necessary for lysosomal degradation (Chakraborty et al, 2017;Weinert et al, 2010). In addition, pHcorrectable genetically encoded reporters such as ClopHensor can be applied, but their complex analysis makes using the small-molecule conjugates more feasible.…”
Section: Third Generationoptimizing the Old Discovering The Newmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to obtain quantitative information, ratiometric reporters that are insensitive to pH are needed. For example, Clensor and MEQ-TMR-dextran have been used to show that high lumenal Cl − , caused by the activity of ClC-7, is necessary for lysosomal degradation (Chakraborty et al, 2017;Weinert et al, 2010). In addition, pHcorrectable genetically encoded reporters such as ClopHensor can be applied, but their complex analysis makes using the small-molecule conjugates more feasible.…”
Section: Third Generationoptimizing the Old Discovering The Newmentioning
confidence: 99%
“…Chloride channels have also been identified that are sensitive to cell volume and extracellular pH, which are involved in signaling following cell swelling and hypoxia, respectively (Qiu et al, 2014;Yang et al, 2019a). Finally, intracellular chloride channels have been implicated in endosomal pH regulation, lysosomal degradation, and endoplasmic reticulum (ER) and mitochondria function (Chakraborty et al, 2017;Jia et al, 2015;Kornak et al, 2001;Mindell, 2012;Novarino et al, 2010;Piwon et al, 2000;Ponnalagu and Singh, 2017;Weinert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While many efforts are dedicated to sensing pH and hydrogen peroxide, many more biomedically relevant analytes may be measured, such as levels of ions, [63,[234][235][236][237] reactive oxygen or nitrogen species, [238][239][240][241][242][243][244][245][246] enzymes, [81,[247][248][249][250][251][252][253][254] glutathione, [255][256][257][258][259][260] and other biomarkers. [261][262][263] An example is the ratiometric hypochlorite sensor developed by Zou et al for the detection of arthritis ( Figure 11A).…”
Section: Sensing Other Biological Markersmentioning
confidence: 99%
“…Градиент протонов также обеспечивает перенос метаболитов, ионов и растворимых субстратов в обоих направлениях [99], он необходим для корректного транспорта вновь синтезированных лизосомных ферментов из комплекса Гольджи в лизосому. В поддержание кислой среды лизосомного люмена также вероятно вовлечены белки семейства CLC (chloride channel), а именно CLC7 [100,101], а также катионный канал муколипин 1 (MCOLN1, известный как TRPML1), и каналы TPC (Two-Pore Channel -двухпоровые каналы) [100], которые опосредуют перенос ионов Ca 2+ и Na + из лизосомы. Недавно идентифицированный лизосомный мембранный белок LAAT1 участвует в транспорте аминокислот лизина и аргинина из лизосомы и в нее.…”
Section: строение лизосомыunclassified